Recent catalysis measurements at IRS. Issue 4 (15th August 2015) - Massuti-Ballester, B.; Pidan, S.; Herdrich, G.; Fertig, M.
Abstract: At the Institute of Space Systems (IRS), experiments have been performed using the high enthalpy, inductively heated plasma generator (IPG) in plasma wind tunnel 3 (PWK3), in order to assess the catalytic behaviour of different materials. Utilising the Upwind Relaxation Algorithm for Non-equilibrium Flows of the University of Stuttgart (URANUS), a methodology for determining catalytic efficiencies by obtaining atomic recombination probabilities γ for high temperature materials, has been developed. This method eliminates the inherent uncertainties produced when using catalytic properties of previously tested materials to infer those of new materials. In this work, eight different candidates for the Thermal Protection System (TPS) of an entry vehicle have been studied, of which six are ceramic materials and the other two are metallic alloys. Thermochemical properties of these specimens are given for surface temperatures between 1000 and 2000 K in pure oxygen and pure nitrogen plasmas. The high enthalpies and relatively low pressure conditions in which these material samples have been tested in PWK3 are relevant for entry applications from Low Earth Orbit (LEO).